Challenges faced by Obstetric Nurse in their daily care activities from the perspective of Resident Nurse (Research, Society and Development, 2025)
The objective of this study is to reflect on some challenges faced by obstetric nurses in their daily care from the perspective of the resident nurse. This is a theoretical and reflective essay constructed from the critical thinking and experiences of the author and specialists, theoretically supported by scientific publications. Three stages of the Problematization Methodology were used to construct this study. As a result, it is worth highlighting that the experiences in the context of training in the Obstetric Nursing Residency Program allowed us to reflect on the challenges faced by obstetric nurses in their daily care. This reflection considered the challenges related to Public Health Strategies and Policies, the challenges related to the Quality of Prenatal Care, and the issues of work overload, limitation of professional autonomy, judgment of obstetric conduct, and insertion of good practices into daily care. It is concluded that the importance of the insertion of the obstetric nurse in services aimed at women's health is evident, guaranteeing her empowerment and autonomy, in order to contribute qualitatively to the reduction of maternal and perinatal morbidity and mortality, the humanization of care, maternal satisfaction, reduction of unnecessary procedures and the demedicalization of childbirth.